ANALISIS KUALITAS JASA, PERSEPSI KEADILAN HARGA, DAN PERSEPSI KEBERSIHAN TERHADAP LOYALITAS PELANGGAN PENGGUNA JASA PANGKAS RAMBUT ASLI GARUT DI DEPOK: ANALYSIS OF SERVICE QUALITY, PERCEPTION OF PRICE FAIRNESS, AND PERCEPTION OF CLEANLINESS ON CUSTOMER LOYALTY OF GARUT ORIGINAL BARBERSHOP SERVICE USERS IN DEPOK - Julian Erlangga; Usep Suhud; Terrylina Arvinta Monoarfa (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The purpose of this study was to examine the effect of service quality, perceived fairness of price, and perceived cleanliness on customer loyalty of users of Asli Garut's hair service. Data collection in this study used an instrument in the form of an online questionnaire. Using a non-probability sampling method using a purposive sampling technique. The sample used in this study was 200 respondents with the criteria of respondents having visited the Asgar barbershop in the last three months and aged 17-55 years. The data analysis technique in this study used Structural Equation Modeling (SEM) with SPSS software version 26 and AMOS version 24. The results of this study indicate that service quality has no positive and significant effect on customer satisfaction, the perception of price fairness has no positive and significant effect on customer satisfaction, perceived cleanliness has no positive and significant effect on customer satisfaction, and there is a positive and significant influence of customer satisfaction on customer loyalty